Prácticas de crianza y el aprendizaje de personal social en los niños de la Institución Educativa Inicial N° 174 Mi Divino Niño, Mariscal Ramón Castilla 2024 - Yovera Monteza, Luz Amparo (2025)
The central objective of this study was to identify the link between parenting practices and the development of learning in the field of social personnel of children belonging to the Initial Educational Institution No. 174 “Mi Divino Niño”, located in Mariscal Ramón Castilla, in the year 2024. This work, of a quantitative nature, was framed within a relational approach, using a non experimental, descriptive and correlational design, with a cross-section. The sample was made up of all parents and children from the aforementioned institution, made up of 74 parents and 74 children. To collect the data, survey and observation techniques were applied, using a questionnaire and an observation guide as tools, which were previously validated by a panel of experts in the field. The findings obtained reflect that the implementation of appropriate parenting practices has a significant impact on children's social personal learning. This conclusion is supported by Spearman's correlation coefficient (Rho = 0.746), which showed a statistically significant relationship at a 95% confidence level.